Trichosporon asahii: A Potential Growth Promoter for C. gallinacea? Implications for Chlamydial Infections and Cell Culture - Erika Ornelas-Eusebio; Fabien Vorimore; Rachid Aaziz; Maria-Lucia Mandola; Francesca Rizzo; Monica Marchino; Chiara Nogarol; Veronica Risco-Castillo; Gina Zanella; Christiane Schnee; Konrad Sachse; Karine Laroucau (Microorganisms)
The cultivation of Chlamydia gallinacea, a recently identified species, is challenging due to the lack of an optimized protocol. In this study, several infection protocols were tested, including different cell lines, incubation temperatures, centrifugation methods and culture media. However, none were successful in field samples. The only exception was a chance co-culture with Trichosporon asahii, a microorganism commonly found in the chicken gut. This suggests that current in vitro methods may not be optimized for this species and that host-associated microorganisms may influence the in vivo growth of C. gallinacea, which is typically found in the chicken gut. These findings raise new questions and highlight the need for further investigation of microbial interactions within the host, particularly to understand their role in the proliferation of chlamydial species.